Chinese-English bilinguals' online compliment response patterns in American (Facebook) and Chinese (Renren) social networking sites. (December 2018) - Eslami, Zohreh R.; Yang, Xinyuan
Abstract: Prior research has documented cross-cultural differences in Western and East Asian societies as reflected in their language use patterns. Research also shows that people with bilingual and bicultural competency can flexibly change their language use patterns in response to different cultural contexts (Canagarajah, 2013). In this paper, we studied compliment response patterns of the same Chinese-English bilinguals in two highly popular social networking platforms (Facebook and Renren). Results showed that while Renren and Facebook are two technically similar platforms, Chinese-English bilingual users who are members of both online cultures flexibly switched and adapted their compliment response patterns in response to the online community in which they were participating. The Chinese-English bilinguals' compliment response patterns were aligned with modesty principles more when they participated in Renren community, and less so when they participated in the Facebook community. Conversely, their compliment response patterns on Facebook were aligned with agreement principle more, and less so when they participated in Renren community. Our findings support that the linkage between language and culture are immutable even in a virtual context, and that bilinguals, who are members of both Renren and Facebook, change their compliment response patterns in response to the online community in which they are participating. The study has both theoretical and methodological significance.